Unlocking Expression: How Extensive Reading Fuels Learners' Willingness to Share Ideas Through Log Writing - Khonamri, Fatemeh; Kurilenko, Viktoria; Podpera , Rastislav (Journal of Education Culture and Society, 2025)
Aim. Providing learners with ample input has become a key method for enhancing language proficiency. Extensive reading (ER) programmes, offering an input-rich environment, play a crucial role in supporting this process. By engaging with large volumes of text, learners improve their language skills, which fosters their ability to communicate, particularly through writing. Method. This study investigated whether participating in an ER program could improve EFL students' willingness to express ideas through written logs. The research involved 45 students enrolled in a reading course at the university, utilizing a mixed-methods approach. Quantitative data were gathered through a self-report questionnaire on willingness to communicate (WTC), while qualitative data were obtained from semi-structured interviews with 15 volunteer students.Results. The findings revealed that self-reported WTC did not necessarily fuel actual communication behavior. While ER did not have a broad role in WTC, the interviewees reported positive roles, particularly in their confidence to share ideas through log writing. Conclusion. A closer analysis showed that the ER program had a positive role in students with higher general WTC levels and other factors also contributed to their willingness to write their ideas in their logs.